2022
DOI: 10.1038/s43856-022-00095-7
|View full text |Cite
|
Sign up to set email alerts
|

An olfactory self-test effectively screens for COVID-19

Abstract: Background Key to curtailing the COVID-19 pandemic are wide-scale screening strategies. An ideal screen is one that would not rely on transporting, distributing, and collecting physical specimens. Given the olfactory impairment associated with COVID-19, we developed a perceptual measure of olfaction that relies on smelling household odorants and rating them online. Methods Each participant was instructed to select 5 household items, and rate their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Findings from our study confirm and extend results from previous studies on the utility of assessing ratings of perceived intensity for actual chemosensory stimuli to evaluate chemosensory dysfunction (Iravani et al, 2020; Snitz et al, 2022). For smell, the intensity of household items was reduced by 47% in the COVID-19+ group compared to the presumably healthy NoSymptoms group.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from our study confirm and extend results from previous studies on the utility of assessing ratings of perceived intensity for actual chemosensory stimuli to evaluate chemosensory dysfunction (Iravani et al, 2020; Snitz et al, 2022). For smell, the intensity of household items was reduced by 47% in the COVID-19+ group compared to the presumably healthy NoSymptoms group.…”
Section: Discussionsupporting
confidence: 88%
“…We also hypothesized that C19+ vs. C19− participants would rate the average odor intensity rating lower, which was supported. Prior studies using self-testing with odor items found in the home (e.g., spices, fragranced products) found odor intensity ratings were predictive of the prevalence of COVID-19 ( 47 , 49 ), highlighting the usefulness of measures of odor intensity to identify smell loss. We also observed that the odor intensity subtest of SCENTinel® was most strongly correlated with active SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%
“…Olfactory assessments range from self-administered odor-based identification of household objects ( Snitz et al, 2021 ) or micro encapsulated familiar odorous substances (University of Pennsylvania Smell Identification Test, UPSIT) ( Moein et al, 2020 ), Sniffin’ Sticks Test ( Lechien et al, 2020 ) or Connecticut Chemosensory Clinical Research Center Test (CCCRC Test) ( Vaira et al, 2020 ). Many of these methods lack precise delivery of odors, which can affect the precision and reliability of behavioral readouts while quantifying olfactory fitness at finer scales.…”
Section: Discussionmentioning
confidence: 99%
“…Studies encompassing the binary yes/no questionnaires, which test the ability to smell easily available odorous objects, visual to analog scale ratings that assess chemosensory abilities and quantitative olfactory detection and discrimination paradigms have indicated olfactory dysfunctions to be one of the strong predictors of COVID-19 ( Bhattacharjee et al, 2020 ; Li et al, 2020 ; Snitz et al, 2021 ; Gerkin et al, 2021 ). Even after the recovery from the infection is achieved, cases of neurocognitive frailty are seen ( Woo et al, 2020 ; Jaywant et al, 2021 ; Burdick and Millett, 2021 ).…”
Section: Introductionmentioning
confidence: 99%